2020
DOI: 10.2147/tcrm.s251495
|View full text |Cite
|
Sign up to set email alerts
|

<p>The Technique of Intradiscal Injection: A Narrative Review</p>

Abstract: Background: Low back pain (LBP) is one of the most common spine diseases and represents the most frequent cause of absence from work in developed countries. Approximately 40% of chronic LBP is related to discogenic origin. The goal of the study is producing a review of literature to describe analytically the techniques of intradiscal injections. Methods: PubMed database was searched for clinical studies with the different key terms: "intradiscal", "injection", "steroid" "procedures", "techniques", "CT", "MRI",… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 41 publications
(478 reference statements)
0
22
0
Order By: Relevance
“…Other measures to prevent the possible risks of discitis include double‐needle technique and preprocedure prophylactic antibiotics or even intradiscal placement of antibiotic 22,23 . The patients should be well informed that even with all the above‐mentioned measures, the risk of discitis still exists 8,18,20 . The following potential complications have been reported in the literature: nerve injury, temporary impaired sensitivity; vitreoretinal hemorrhages; thunderclap headache related to pneumoencephalus as a consequence of inadvertent intrathecal puncture; and 1 case of vertebrobasilar stroke.…”
Section: Discussionmentioning
confidence: 99%
“…Other measures to prevent the possible risks of discitis include double‐needle technique and preprocedure prophylactic antibiotics or even intradiscal placement of antibiotic 22,23 . The patients should be well informed that even with all the above‐mentioned measures, the risk of discitis still exists 8,18,20 . The following potential complications have been reported in the literature: nerve injury, temporary impaired sensitivity; vitreoretinal hemorrhages; thunderclap headache related to pneumoencephalus as a consequence of inadvertent intrathecal puncture; and 1 case of vertebrobasilar stroke.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, a narrative review by Migliore et al describes different intradiscal injection techniques, including guidance by fluoroscopy, CT, and CT plus fluoroscopy. Comparison of various efficacy and safety outcomes found that results were not easily comparable due to differences in highly variable procedural techniques, study designs, and a limited number of studies, thus, warranting more research on the efficacy and safety of these procedures [ 59 ].…”
Section: Discographymentioning
confidence: 99%
“…Such intervention has shown little progress in IVDD treatment over the past few decades, resulting in an increase in administration of therapeutic agents through direct intradiscal injection. [20][21][22] The intradiscal injection is a technique widely used in the LBP management of patients who are not responsive to rehabilitative and medical treatments. [20][21][22] Moreover, because repeated administrations of senolytic drugs for an extended period of time are generally required for effective removal of senescent cells in vivo, [6,[9][10][11] multiple intradiscal injections would be required.…”
Section: Introductionmentioning
confidence: 99%
“…[20][21][22] The intradiscal injection is a technique widely used in the LBP management of patients who are not responsive to rehabilitative and medical treatments. [20][21][22] Moreover, because repeated administrations of senolytic drugs for an extended period of time are generally required for effective removal of senescent cells in vivo, [6,[9][10][11] multiple intradiscal injections would be required. [16] However, multiple intradiscal injections to IVD may cause clinical disc problems such as discitis (infection of the discs) and potentially accelerate IVDD.…”
Section: Introductionmentioning
confidence: 99%